Package Evolvability and its Relationship with Refactoring - Mubarak, Asma; Counsell, Steve; Hierons, Rob; Hassoun, Youssef (Electronic Communications of the EASST, 2008)
In this paper, we address a set of research questions investigating trends in changes to an open-source system (OSS). An interesting âpeak and troughâ effect trend was found to exist in the system studied, suggesting that developer activity comprises of a set of high and low periods. Trends in overall changes applied to the system were complemented with empirical evidence in refactoring data for the same system; this showed a similar peak and trough effect but at different versions of the same system. This result suggests a contrasting motivation between regular maintenance practice and that of refactoring. Our analysis of high-level package trends informed some interesting cross-comparisons with refactoring practice, and some insights into why refactoring might be applied after a burst of regular change activity, rather than consistently. We use data extracted from seven Java OSS as a basis for our refactoring analysis.